Heat mutagenesis in bacteriophage T4: the transition pathway. - Baltz, R H (1976)
G-C leads to A-T transitions are induced by heat, and arise from the deamination of cytosine (5-hydroxymethylcytosine in the case of bacteriophage T4) generating uracil. The reaction is proton-catalyzed, and is also characteristic of acid mutagenesis. Mutation rates and activation energies of mutation are site-specific, and are presumably influenced by neighboring bases. Rates of heat-induced mutation in bacteriophage T4 under conditions of temperature, pH, and ionic strength similar to those prevailing in higher eukaryotic cells suggest that heat mutagenesis may present a serious challenge to organisms with large genomes, and may comprise an important determinant of the rates of spontaneous mutation.